TASHRIFAN JOMBANG: Telaah Epistemologi Kitab Al-Amtsilah Al-Tashrifiyah Karya Kyai Ma’shum Bin Ali - Moch. Nurcholis; Fathoni Fathoni (Muróbbî: Jurnal Ilmu Pendidikan, 2022)
Abstract: Sharaf science as a part of Arabic grammar can be said to be compulsory science in Islamic boarding schools, whether salaf, modern, or integrated. This study will examine the book of tashrif entitled Al-Amtsilah Al-Tashrifiyah by Kyai Ma'shum bin Ali by focusing on the epistemological aspect as far as the nature of tashrif is concerned, the systematics and model of preparation, and the sources and validity of tashrif scholarship in it. This qualitative research utilizes library data through documentation techniques. Content analysis and descriptive-analytic techniques were used in this study to analyze the collected data. Meanwhile, in drawing conclusions, Miles and Hubermen's interactive model is used. This research concludes two things. First, the book of Al-Amtsilah Al-Tashrifiyah is basically a book that contains a collection of examples of the interpretation of a word, both terminology and lughawi patterns. The systematics of this book starts with an example of word interpretation in a term tashrif pattern and is followed by a lughawi tashrif. The presentation of the tasfhrifan book uses a combination of two models, namely tables and songs. Second, the compilation of the book Al-Amtsilah Al-Tashrifiyah refers to the formulation of tashrif which is theoretically-coceptual in accordance with the sharaf rules contained in the books of Nadham al-Maqshud, al-Alfiyyah Ibn Malik, Syarh Qathr al-Nada, Awdlah al- Masalik, The Book of Sibawaih. More than that, the order of pentasrifan, especially the terminology, in the book Al-Amtsilah Al-Tashrifiyah is identical to the idea and pattern of pentasrifan developed by Imam Sibawaih.